Omentin Val/Val genotype increases predisposition to acne vulgaris without changing omentin serum level - Soguktas, Hatice; Yaykasli, Kursat Oguz; Turan, Hakan; Kaya, Ertugrul; Yaykasli, Emine (Cellular and Molecular Biology, 2018)
Acne vulgaris is the most frequent and multifactorial inflammatory skin disorder in all races. Obesity is considered to be a risk factor for acne due to its contribution to inflammation. The involvements of inflammatory (leptin and resistin) and anti-inflammatory (adiponectin) adipokines in the pathogenesis of acne were reported. Omentin resembles adiponectin in terms of having inhibitory effect on tumor necrosis factor-Î± (TNF-Î±) induced inflammation, a vital process in the acne formation. This study was designed to investigate the putative involvement of omentin in acne formation. The genotyping was performed by restriction fragment length polymorphism (RFLP) method. Serum omentin protein levels were analyzed by enzyme-linked immunosorbent assay (ELISA). Serum omentin level was not significantly changed between groups. However, the decreased serum omentin level was observed as the mean value of BMI increased. The Asp/Asp, Val/Asp and Val/Val genotypes distributions for control and patient groups (19[17.4%], 22[20.2%], and 3[2.8%] respectively, vs. 31[28.4%], 25[22.9%], and 9[8.3%], respectively) were obtained. The Val/Val (mutant homozygote) genotype was found nearly 1.8 times more in the patient group (p=0.403, OR=1.839 (0.442-7.653)). This is the first time to clarify a linkage between anti-inflammatory omentin and acne vulgaris. Omentin Val109Asp polymorphism affects the overall function of the protein. In conclusion, omentin Val/Val (mutant homozygote) genotype increases predisposition to acne vulgaris by probably disrupting overall protein function of omentin.